PARENTAL INVOLVEMENT IN THE CHILD DEVELOPMENT PROCESS AT HOME - Kazlauskiene, Ausra; Kravčenkaitė, Justina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article analyses the involvement of parents participating in the child's education process. The semi-structured interview method was chosen to collect the survey data. The content analysis method was used for the analysis of the research data. During the study, the aim was to find out what were the possibilities of parental involvement in the child's education process, and which parents were satisfied with the needs of the children. Parents who live in cities and villages are selected by the participants of the study. Data from a qualitative research analysis suggests that parents are divided into different parties to the opposition, where no one wants to engage in the child's educational process, while others actively contribute to the process of child's education. It has been disclosed that the lack of time planning and other factors make it impossible to contribute or minimally contribute to joint activities with the child.